Molecular epidemiology, genetic diversity and antimicrobial resistance of Staphylococcus aureus isolated from chicken and pig carcasses, and carcass handlers - Okorie-Kanu, Onyinye J.; Anyanwu, Madubuike U.; Ezenduka, Ekene V.; Mgbeahuruike, Anthony C.; Thapaliya, Dipendra; Gerbig, Gracen; Ugwuijem, Ejike E.; Okorie-Kanu, Christian O.; Agbowo, Philip; Olorunleke, Solomon; Nwanta, John A.; Chah, Kennedy F.; et al. (PloS one, 2020)
The epidemiology of Staphylococcus aureus in food animals, associated products, and their zoonotic potential in Nigeria are poorly understood. This study aimed to provide data on the prevalence, genetic characteristics and antimicrobial resistance of S. aureus isolated from chicken and pig carcasses, and persons in contact with the carcasses at slaughterhouses in Nigeria. Surface swabs were collected randomly from 600 chicken and 600 pig carcasses. Nasal swabs were collected from 45 workers in chicken slaughterhouses and 45 pig slaughterhouse workers. S. aureus isolates were analyzed by spa typing. They were also examined for presence of the Panton-Valentine Leucocidin (PVL) and mecA genes, as well as for antimicrobial resistance phenotype. Overall, 53 S. aureus isolates were recovered (28 from chicken carcasses, 17 from pig carcasses, 5 from chicken carcass handlers and 3 from pig carcass handlers). Among the isolates, 19 (35.8%) were PVL-positive and 12 (22.6%) carried the mecA gene. The 53 isolates belonged to 19 spa types. The Based Upon Repeat Pattern (BURP) algorithm separated the isolates into 2 spa-clonal complexes (spa-CC) and 9 singletons including 2 novel spa types (t18345 and t18346). The clonal complexes (CC) detected were CC1, CC5, CC8, CC15, CC88 and CC152. CC15-related isolates represented by spa type t084 (32.1%) and CC5 represented by spa type t311 (35.3%) predominated among isolates from chicken carcasses/ handlers, and pig carcasses/ handlers, respectively. Multidrug resistance exhibited by all the CC except CC8, was observed among isolates from chicken carcasses (64.3%), pig carcasses (41.2%), handlers of chicken meat (40.0%) and handlers of pork (33.3%). All the CC showed varying degrees of resistance to tetracycline while CC15 and CC5 exhibited the highest resistance to sulphamethoxazole/trimethoprim and erythromycin, respectively. The predominant antimicrobial resistance pattern observed was penicillin-tetracycline-sulphamethoxazole/trimethoprim (PEN-TET-SXT). In conclusion, food animals processed in Enugu State in Southeast Nigeria are potential vehicles for transmission of PVL-positive multiple-drug resistant S. aureus and methicillin-resistant S. aureus from farm to slaughterhouse and potentially to the human population. Public health intervention programs at pre- and post-slaughter stages should be considered in Nigerian slaughterhouses.